Functionalised type-I collagen as a hydrogel building block for bio-orthogonal tissue engineering applications. Issue 2 (14th December 2015) - Ravichandran, R.; Islam, M. M.; Alarcon, E. I.; Samanta, A.; Wang, S.; Lundström, P.; Hilborn, J.; Griffith, M.; Phopase, J.
Abstract : Modulating the hydrogel properties from injectable to implantable scaffolds using the bio-orthogonal thiol-Michael addition click reaction. Abstract : In this study, we derivatized type I collagen without altering its triple helical conformation to allow for facile hydrogel formation via the Michael addition of thiols to methacrylates without the addition of other crosslinking agents. This method provides the flexibility needed for the fabrication of injectable hydrogels or pre-fabricated implantable scaffolds, using the same components by tuning the modulus from Pa to kPa. Enzymatic degradability of the hydrogels can also be easily fine-tuned by variation of the ratio and the type of the cross-linking component. The structural morphology reveals a lamellar structure mimicking native collagen fibrils. The versatility of this material is demonstrated by its use as a pre-fabricated substrate for culturing human corneal epithelial cells and as an injectable hydrogel for 3-D encapsulation of cardiac progenitor cells.